Controversies and expectations for the prevention of GVHD: A biological and clinical perspective - Watkins, Benjamin; Williams, Kirsten M. (Frontiers in Immunology, 2022)
Severe acute and chronic graft versus host disease (GVHD) remains a major cause of morbidity and mortality after allogeneic hematopoietic cell transplantation. Historically, cord blood and matched sibling transplantation had been associated with the lowest rates of GVHD. Newer methods have modified the lymphocyte components to minimize alloimmunity, including: anti-thymocyte globulin, post-transplant cyclophosphamide, alpha/beta T cell depletion, abatacept. These agents have shown promise in reducing severe GVHD, however, can be associated with increased risks of relapse, graft failure, infections, delayed immune reconstitution. Nonetheless, these GVHD prophylaxis strategies have permitted expansion of donor sources, especially critical for those of non-Caucasian decent who previously lacked transplant options. This review will focus on the biologic mechanisms driving GVHD, the method by which each agent impacts these activated pathways, and the clinical consequences of these modern prophylaxis approaches. In addition, emerging novel targeted strategies will be described. These GVHD prophylaxis approaches have revolutionized our ability to increase access to transplant and have provided important insights into the biology of GVHD and immune reconstitution.